An Improved Method for the Synthesis of Lipopeptide TLR2-Agonists Using Click Chemistry - Wright, Tom H.; Brooks, Anna E. S.; Didsbury, Alicia J.; McIntosh, Julie D.; Burkert, Kristina; Yeung, Ho; Williams, Geoffrey M.; Dunbar, P. Rod; Brimble, Margaret A. (Synlett, 2013)
S-[2,3-Bis(palmitoyloxy)propyl]cysteine (Pam2Cys) is a synthetic lipid motif known to act as a TLR2 agonist when incorporated into peptide vaccines. Herein, we report the synthesis of Pam2Cys-containing, propargyl-functionalised ‘clickable’ building blocks and their conjugation with azide-functionalised antigenic peptides using click chemistry. This method facilitates the fully convergent preparation of self-adjuvanting lipopeptides for use as vaccines.
Keywords: lipopeptides; CuAAC; synthetic lipids; adjuvant; click chemistry